Comparative analysis of muscle synergies in gait of stroke patients and healthy controls - Komaris, Dimitrios-Sokratis; Tsaopoulos, Dimitrios; Risvas, Konstantinos; Nikolopoulos, Spiros; Baltzopoulos, Vasilios; Maganaris, Constantinos; Kompatsiaris, Ioannis (Frontiers in Human Neuroscience, 2025)
IntroductionThis study analyzed muscle synergies in subacute stroke patients’ gait, comparing paretic and non-paretic limbs with healthy individuals, and explored the structure and temporal activation of synergistic muscle activation patterns.MethodsMuscle synergies were computed from EMG data of 12 muscles in 138 able-bodied adults and 50 stroke survivors using non-negative matrix factorization, analyzing 350 control strides, 319 paretic strides, and 337 non-paretic strides. Temporal activation coefficients of the muscle synergies between groups of strides were also compared using cross-correlation analysis.ResultsThe extracted muscle synergies were consistent in composition across all groups of control and stroke subjects, with four synergies identified in gait cycles on average. The comparison of the synergies’ temporal activation returned indexes (r) ranging from 0.60 to 0.74, with differences existing in the duration and timing of the activations of the hip flexors and knee extensors, dorsal flexors, and plantar flexors.DiscussionOur findings suggest a certain degree of preserved motor function in stroke patients’ gait, even in the presence of recent hemiparesis, but with evident alterations in the synergies’ temporal activation. Stroke rehabilitation by targeting abnormal muscle synergy activations may help shape personalized treatment plans.